An Overview of Biometric Technologies and Its Benefits - D, Gayathri; Uma Rani, R (International Journal of Computer Sciences and Engineering, 2019)
Biometric technology is becoming a standard security feature in large businesses. In the modern networked society, there is an ever growing need to determine or verify the identity of a person. Where authorization is necessary for any action, be it collecting a child from child-care facilities or boarding an aircraft, authorization is almost always vested in a single individual or a class of individuals. There are a number of existing methods, used by society or automated systems to verify identity. Traditional existing methods can be grouped into three classes: (i) possessions; (ii) knowledge and (iii) biometrics. Biometrics is the science of identifying or verifying the identity of a person based on physiological or behavioral characteristics. It provides additional layer of security via its strong authentication process. This innovation allows compromised premises to quickly identify intruders. As the technology world is evolving there are more and more trends and demand in the field of identity management. All these trends and demands are generated from one basic need – the need for a more accurate and secure way of identifying an individual. The intelligent ones are already learning to adopt with these trends in order to gain competitive advantage. This Paper brings about the recent trends in Biometric Technologies and its applications.